2021
DOI: 10.3389/fphys.2021.627837
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial Reactive Oxygen Species and Their Contribution in Chronic Kidney Disease Progression Through Oxidative Stress

Abstract: Mitochondria are known to generate approximately 90% of cellular reactive oxygen species (ROS). The imbalance between mitochondrial reactive oxygen species (mtROS) production and removal due to overproduction of ROS and/or decreased antioxidants defense activity results in oxidative stress (OS), which leads to oxidative damage that affects several cellular components such as lipids, DNA, and proteins. Since the kidney is a highly energetic organ, it is more vulnerable to damage caused by OS and thus its contri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
117
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 199 publications
(141 citation statements)
references
References 118 publications
(176 reference statements)
1
117
0
2
Order By: Relevance
“…Damaged mitochondria are the main source of intracellular ROS due to the decrease in their antioxidant activity [ 42 ]. The effect of C3a on the activity of the mitochondrial antioxidant enzyme superoxide dismutase 2 (SOD2), which plays a key role in the mitochondrial defense against ROS production [ 43 ] was evaluated by western blot analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Damaged mitochondria are the main source of intracellular ROS due to the decrease in their antioxidant activity [ 42 ]. The effect of C3a on the activity of the mitochondrial antioxidant enzyme superoxide dismutase 2 (SOD2), which plays a key role in the mitochondrial defense against ROS production [ 43 ] was evaluated by western blot analysis.…”
Section: Resultsmentioning
confidence: 99%
“…The main conclusion of this study is that an absence of robust data to either support or dismiss the hypothesis that inhibition of oxidative stress slows or ameliorates CKD progression has been determined. As a corollary, the role of oxidative stress in CKD progression remains uncertain, despite several authors having suggested its participation in CKD pathophysiology [ 9 , 54 , 56 ]. Future studies need to be optimized with matched data from renal function and oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…However, in normal circumstances, the renal antioxidant system, including CAT, GPX, and SOD, corrects any ROS-facilitated injury. Renal injury is characterised by the excessive production of mitochondrial ROS [92]. Specific biomolecules undergo oxidation when there is an imbalance in the redox systems, resulting in anatomical and structural modifications of these molecules.…”
Section: Chronic Kidney Disease (Ckd)mentioning
confidence: 99%